Detecting Enteral Nutrition Residues and Microorganism Proliferation in Feeding Tubes via Real-Time Imaging. (April 2017) - Yamaoka, Ippei; Kagawa, Tomohiro; Mizugai, Kazuya; Ebisu, Goro
Background: Enteral nutrition (EN) residues that persist in feeding tubes provide substrates for microorganisms to proliferate and occlude the tubes. Visible EN residues in tubes are easily identified, but smaller residues can persist. We developed a new imaging technique to visualize EN residues and proliferation of microorganisms in feeding tubes. Materials and Methods: (1) Feeding tubes containing EN labeled with fluorescent dye and either with or without various types or amounts of thickeners were flushed once with water and then seeded with Pseudomonas aeruginosa Xen05 with recombinant luciferase DNA. (2) Because EN fluoresces intrinsically, EN in the feeding tubes without fluorescent dye was repeatedly flushed until the intrinsic fluorescence levels reached background levels. Fluorescent images of EN residues and bioluminescent images of microorganisms were acquired via an optical imaging system. Results: (1) Fluorescence images showed that the amount of EN residues increased at various sites in tubes depending on EN viscosity and the thickening agent, and bioluminescence images showed that microorganism proliferation was associated with a commensurate increase in EN residues. (2) The intrinsic fluorescence of EN also enabled the detection of EN residues in tubes even in the absence of fluorescence dye. Higher EN viscosity required more flushes to reach undetectable levels. Conclusion: EN residues and microorganism proliferation in enteral feeding tubes were detected on fluorescence and bioluminescence images, respectively. This simplified approach allowed the real-time visualization of EN residues and microorganisms in feeding tubes.